A rare case report of chronic suppurative osteomyelitis of the mandible in modern era of broad spectrum antibiotics - Gupta, Shilpi; Saikia, N. J.; Singh, Anurag (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Historically, osteomyelitis of the jaw was a common complication of odontogenic infection (infections of the teeth). The term osteomyelitis refers to an inflammation of cortex and medulla of the bone that can develop in the jaw after any infection of the oral cavity. Since the introduction of potent antibiotics, the incidence of osteomyelitis has been dramatically decreasing. This case report describes an interesting presentation of chronic suppurative osteomyelitis of the mandible in a 73 years old male patient from North Eastern part of India. Investigations revealed chronic osteomyelitis of right ramus and body of mandible. The treatment included a pre surgical course of antibiotics followed by right side hemimandibulectomy and again post-operative antibiotics. The post-operative healing was uneventful. Detailed discussion of etiology, risk factor, symptoms, signs, management and prevention has been done in this case report. We conclude that surgical debridement in addition to empirical antibiotics should be considered as an early approach for treating such cases.